Inovasi Pemetaan Desa dengan Google Maps: Implementasi di Kawasan Pengunungan - Fauzi; Nelud Daraajatul Aliyah (Yayasan Literasi Altruis Khatulistiwa, 2025)
All elements of a village, including its potential, community culture, and natural and human resources, are important assets that belong to the village and require development, promotion, and dissemination efforts to the wider community. With Google Maps, the spatial planning of villages, including mosques, schools, health facilities, and other important places, has become more efficient and easier to access. The objective of this research is to digitize the area using Google Maps to facilitate others in obtaining information, promoting businesses, and improving accessibility and village development. This research was conducted in three villages near the research site: Batobella Village, Batogubang Village, and Geger Village in Geger Sub-district, Bangkalan District, using the Asset-Based Community Development (ABCD) method. This approach was chosen because it focuses on empowering communities through mapping the potential and local assets of each village. This community service initiative has successfully conducted digital mapping using Google Maps of important locations in the three surrounding villages, including places of worship, education, health facilities, community-owned businesses, and other strategic locations.